Design and Build of Communication Protocol Trainer Tools on Networks between PLCs and HMIs - Rudiansyah, Hendy; Ridwan, Ridwan; Purnomo, Wahyudi; Hadiani, Dini; Arrizik, Muhammad Zidan (Journal La Multiapp, 2024)
With the rapid advancement of science and technology, the role of technology in industry is also increasing, particularly through automation that simplifies and enhances work process efficiency. To support this development, education plays a crucial role in enhancing students' competencies. One relevant subject in industrial technology is Programmable Logic Controller (PLC). In PLC education, trainer tools are used to help students understand industrial control concepts. At Politeknik Manufaktur Bandung, particularly in the Mechatronics and Automation Engineering Technology programs, the use of PLC trainers is still limited to basic input-output features. Survey results show that most students only understand Ethernet communication protocol and have never connected more than one PLC in a single system, resulting in a limited understanding of inter-PLC communication. This research aims to develop a trainer that teaches various PLC communication protocols, including Controller Link, DeviceNet, Serial RS-232C, and Ethernet, with inter-PLC and HMI communication implementation. The system uses three PLCs, where an Omron CP1H PLC as the master uses Controller Link to communicate with another Omron CP1H PLC as a slave, DeviceNet for remote slave devices, Serial RS-232C to communicate with an Omron CJ2M PLC as a slave, and Ethernet connected to Human Machine Interfaces (HMI) Omron NB7W and Kinco GL070E for PLC data monitoring. Based on the assessment results, the overall trainer tool evaluated received an effectiveness score of 95.1% from 6 aspects of the assessment. This trainer is expected to enhance students’ understanding of PLC communication protocols and their applications in integrated systems.